Supplementation of mixed Lactobacillus alleviates metabolic impairment, inflammation, and dysbiosis of the gut microbiota in an obese mouse model - Hou, Shulin; Li, Ruining; Zhang, Yunyun; Liang, Ping; Yang, Haishan; He, Huili; Wang, Lei; Sun, Yaojun; Jin, Tianru; Liu, Zhizhen; Xie, Jun (Frontiers in Nutrition, 2025)
IntroductionObesity is a complex metabolic disease, which is often accompanied with impaired glucose and lipid metabolism and chronic inflammation. Probiotics have been considered as a strategy for treating obesity, while the genus of Lactobacillus is the most commonly tested and approved probiotics. Some multi-strain probiotics were proven to produce synergistic effects on treating obesity as compared to mono-strain ones.MethodsThe purpose of this study was to investigate the anti-obesity effect of a new probiotic formation contained Lactobacillus plantarum L14, Lactobacillus paracasei L9, Lactobacillus rhamnosus GG, and Lactobacillus sakei X-MRS-2, designated as L-PPRS. Multi-strain probiotics L-PPRS was shown to have a better antiadipogenic effect than mono-strain probiotics in 3T3-L1 cell. Subsequently, L-PPRS was orally supplemented to a high-fat diet (HFD) induced obese mouse model for two kinds of treatment course, a short-term (8 weeks) one and a long-term (12 weeks) one.ResultsWe found that intervention of L-PPRS not only significantly inhibited weight gain in HFD-fed mice, but also improved glucose tolerance, insulin sensitivity and reduced serum lipid levels. Furthermore, L-PPRS intervention reduced fat accumulation in the adipose tissue and the liver, and ameliorated the antioxidant capacity of liver in HFD-fed mice. L-PPRS intervention modulated the expression of lipid-metabolic genes, and exhibited excellent anti-inflammatory effect. In addition, L-PPRS intervention restored the dysbiosis of gut microbiota via reducing the Firmicutes/ Bacteroidetes ratio, and increasing the abundance of beneficial intestinal bacteria. In conclusion, this study proved that L-PPRS could effectively prevent the development of obesity and its associated abnormalities, and the long-term supplementation of L-PPRS provided a more profound benefit than the short-term.DiscussionThis study highlights the potential of L-PPRS as an effective anti-obesity strategy.